Relaciones socio-afectivas entre docentes y niños y niñas, en el proceso de enseñanza -aprendizaje del primer año de educación básica de las escuelas fiscales mixta Eva Esperazna Batallas de Falquez y John F. Kennedy, de la ciudad de Pasaje, en el período lectivo 2012-2013. - Morocho Benavides, Priscila Estefanía (2013)
The Socio-Affective relations requires that mediation efforts are maximized the potential of the interaction: teacher-student, student-as, family-student-learners and social groups It is part of the adaptive behavior of the subject. In childhood they are developing forms and relationships that affect largely the degree of affection with that work and children interact in their environment. The positive socio-emotional development creates the foundation for language learning and skills development or social ability to interact with other cultures.